Structural, Optical and Electrical Properties of p-CuS:Cu+and n-CuS:Sn4+ Films Deposited with a Chemical Bath Deposition - He, Haiyan; Huang, Jianfeng; Fei, Jie; Lu, Jing (Recent Patents on Nanotechnology, 2015)
This work presents the manufacturing and potential application of the CuS films in recent literature and patents and then focus on the chemical bath depostion of p-CuS: Cu+and n-CuS: Sn4+ filmsat room temperature by controlling S/Cu molar ratio in the bath solution and doping Cu+ and Sn4+ cations, respectively. The CuS:Cu+and CuS:Sn4+ films with S/Cu molar ratio larger and less than the stoichiometric ratio showed p-type and n-type electrical conduction, respectively, and low electrical resistivity of 1.31×10-3 Ω·cm and 0.73-0.80×10-3 Ω·cm, respectively. Moreover, the films had the average transmittance of 20.1-30.1 % in 290-1100 nm. The direct allowed band gaps and indirect allowed optical band gap energies of the films were estimated to be in the ranges of 2.58-2.63 eV and 1.6-1.78 eV, respectively. The extinction coefficient, refractive index, dielectric constant, and optical conductivity of the films were calculated with the transmittance and reflectance spectra.
Keywords: A. nanostructures